1998
DOI: 10.1002/(sici)1521-4141(199812)28:12<4020::aid-immu4020>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Parasite dose determines the Th1/Th2 nature of the response toLeishmania major independently of infection route and strain of host or parasite

Abstract: Leishmania major causes cutaneous leishmaniasis in mice and man. Infection of mice with relatively low or high numbers of parasites leads respectively to parasite containment, associated with a Th1, cell-mediated response, or progressive disease, associated with a Th2, antibody response in all circumstances studied. These include different parasite strains, different routes of infection, and different hosts previously classified as susceptible, resistant or of intermediate susceptibility. This dose dependency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
105
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(113 citation statements)
references
References 32 publications
7
105
0
1
Order By: Relevance
“…Here we demonstrate that even before different antigen-presenting cells begin to prime adaptive immunity, the site of inoculation immediately influences the effective dose of L. major parasites that establishes infection. The parasite dose has far-reaching implications for Leishmania infections, including the nature of the adaptive immune response, and is likely one of the most important variables in determining the kinetics and outcome of infection (6,36,(44)(45)(46)(47)(48)). Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Here we demonstrate that even before different antigen-presenting cells begin to prime adaptive immunity, the site of inoculation immediately influences the effective dose of L. major parasites that establishes infection. The parasite dose has far-reaching implications for Leishmania infections, including the nature of the adaptive immune response, and is likely one of the most important variables in determining the kinetics and outcome of infection (6,36,(44)(45)(46)(47)(48)). Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6).…”
Section: Discussionsupporting
confidence: 90%
“…The parasite dose has far-reaching implications for Leishmania infections, including the nature of the adaptive immune response, and is likely one of the most important variables in determining the kinetics and outcome of infection (6,36,(44)(45)(46)(47)(48)). Our observations demonstrate that the number of parasites that establishes infection must be considered in interpreting the influence of the site of infection, as suggested previously (6). We and others have demonstrated that the relative differences in parasite load or lesion size following inoculation at different sites or with different doses of parasites can change depending on the time of analysis (1,3,7,36,48).…”
Section: Discussionmentioning
confidence: 99%
“…The paradigm for the CD4 + T-helper 1 (Th1)/Th2 dichotomy is largely based, 2 . Conflicting data may arise in part because different parasite strains or species are being examined, different tissue target (the mice's footpad, the ear, or base of the tail) are being infected, and different doses ("low" 1x10 2 and "high" 1x10 6 ) of metacyclic promastigotes have been inoculated 20,27,28 . In addition immunological studies carried out in humans did not reproduce the Th1/Th2 dichotomy described in the L. major, C57BL/6 and the BALB/c mouse model of CL 18,23,24 .…”
Section: This Is the First Study That Examines P Yucatanicus Clinicamentioning
confidence: 95%
“…Ag dose is also known to affect the Th1/Th2 phenotype of the ensuing response. Most in vivo observations show that lower and higher doses, respectively, favor the generation of Th1 and Th2 cells (5,(25)(26)(27)(28)(29)(30), although some in vitro observations are inconsistent with this conclusion (31).…”
mentioning
confidence: 99%